HOW THE PERFORMANCE OF A DC MOTOR SYSTEM IS IMPACTED BY NOISE - admin journal; Rizky Fitra Kurniawan; Muhammad Hanif Mudhoffar; Anggara Trisna Nugraha; Laili Agustin Widyaningrum (Pusat Penelitian dan Pengabdian Masyarakat (P3M) - PPNS, 2023)
The rapid and effortless evolution in different realms of this era includes the sustainable advancement of technology, exerting significant influence on various facets. The expansive nature of technology and information underscores its versatility. Observing these progressions, the ongoing development of science emerges as an inevitable outcome, drawing upon existing knowledge and perpetuating studies to enhance future functionality. The optimization of knowledge through the examination of its evolution proves instrumental in facilitating innovation for future generations, ensuring more efficient and ergonomic utilization. So, considering the substantial electricity demands in the industry, which rely on evenly spread energy sources, it's crucial to find a method for efficiently managing this demand. This involves delving into the realm of science, particularly in the context of propulsion engines. Through research, one can explore how system optimization impacts the effectiveness of control methods like LQR and LQT, especially when additional noise is introduced to the DC motor load system.